Seed Characterization and Scanning Electron Microscope (SEM) Morphology of the Testa of Three Groups of Argentine Opuntia ficus-indica (Cactaceae) - Degano, C.; Alonso, M.E.; Ochoa, J.; Catan, A. (Journal of the Professional Association for Cactus Development, 1997)
The external morphology of the seeds and the SEM structure of the epicuticular waxes of seeds of three groups of O. ficus-indica naturalized to Argentina, i.e., a spiny red-fruited variety, a spiny orange fruited variety and a spineless yellow-fruited variety, were studied. The seeds of the three groups are not differentiated easily with the naked eye. However, hairs can be observed on the surface of the seeds of the red-fruited group with the aid of a stereomicroscope. All three types of O. ficus-indica have a hilum in the apical or subapical position, but only the red and orange types have an aril. Different kinds of epicuticular waxes and wax granules were observed on the seeds of these Opuntias with SEM techniques. However, the differences in epicuticular wax characteristics were not sufficient to characterize them according to species.